2008
DOI: 10.1016/j.molcel.2008.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Transient Reversal of RNA Polymerase II Active Site Closing Controls Fidelity of Transcription Elongation

Abstract: To study fidelity of RNA polymerase II (Pol II), we analyzed properties of the 6-azauracil-sensitive and TFIIS-dependent E1103G mutant of rbp1 (rpo21), the gene encoding the catalytic subunit of Pol II in Saccharomyces cerevisiae. Using an in vivo retrotransposition-based transcription fidelity assay, we observed that rpb1-E1103G causes a 3-fold increase in transcription errors. This mutant showed a 10-fold decrease in fidelity of transcription elongation in vitro. The mutation does not appear to significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
330
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(356 citation statements)
references
References 54 publications
23
330
2
1
Order By: Relevance
“…The closure of TL is critical for pol II catalytic activity as well as transcriptional fidelity (27)(28)(29)(30)(36)(37)(38)(39). For the wild-type 3′-5′ linkage system, the high transcriptional fidelity is due to pol II's capacity to incorporate matched NTP in a fast and TL-dependent manner (in which TL can achieve a closed conformation during nucleotide addition process) and incorporate mismatched NTP in a slow and TL-independent manner (in which TL remains at an open conformation during nucletotide addition).…”
Section: Discussionmentioning
confidence: 99%
“…The closure of TL is critical for pol II catalytic activity as well as transcriptional fidelity (27)(28)(29)(30)(36)(37)(38)(39). For the wild-type 3′-5′ linkage system, the high transcriptional fidelity is due to pol II's capacity to incorporate matched NTP in a fast and TL-dependent manner (in which TL can achieve a closed conformation during nucleotide addition process) and incorporate mismatched NTP in a slow and TL-independent manner (in which TL remains at an open conformation during nucletotide addition).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the TL acts as a critical component of kinetic selection of correctly matched NTP substrates by promoting their faster incorporation in comparison with incorrect substrates (12,30). In support of this hypothesis, substitution of a residue in the ␣-helix at the base of the TL that affected the equilibrium between the closed and open TL conformations decreased fidelity of RNA synthesis by Sce RNA-PII (30). Our results suggest that the F loop also contributes to substrate selection by promoting proper folding of the TL.…”
Section: Discussionmentioning
confidence: 99%
“…1, compare a and b). In addition, Kashlev's and our laboratory showed that the ability of the TL to adopt two conformations is the prerequisite for the high accuracy of RNA synthesis (Kireeva et al, 2008;. In the 'induced fit' mode, the correct NTP induces folding of the TL, which, in turn, provides the physical surface complementary to the NTP and thus stabilizes the transition state of the reaction.…”
mentioning
confidence: 99%